2009
DOI: 10.1103/physrevd.79.023518
|View full text |Cite
|
Sign up to set email alerts
|

Radio constraints on dark matter annihilation in the galactic halo and its substructures

Abstract: Annihilation of Dark Matter usually produces together with gamma rays comparable amounts of electrons and positrons. The e + e − gyrating in the galactic magnetic field then produce secondary synchrotron radiation which thus provides an indirect mean to constrain the DM signal itself. To this purpose, we calculate the radio emission from the galactic halo as well as from its expected substructures and we then compare it with the measured diffuse radio background. We employ a multi-frequency approach using data… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
83
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(91 citation statements)
references
References 66 publications
8
83
0
Order By: Relevance
“…We expanded upon the current literature in several aspects: a) by using both a semi-analytical approach to model the particle propagation in the intergalactic medium [32,33], and a full numerical analysis based on the GALPROP code [19,20], benefiting from the strengths of both in particular aspects of the work, b) considering intermediate Galactic latitudes, where the DM profiles are more robustly constrained, and c) taking into account the large astrophysical uncertainties on the magnetic fields. We have shown that synchrotron emissions can give very pertinent bounds on DM annihilation cross section, confirming previous results [12,[14][15][16].…”
Section: Conclusion and Prospectssupporting
confidence: 90%
See 1 more Smart Citation
“…We expanded upon the current literature in several aspects: a) by using both a semi-analytical approach to model the particle propagation in the intergalactic medium [32,33], and a full numerical analysis based on the GALPROP code [19,20], benefiting from the strengths of both in particular aspects of the work, b) considering intermediate Galactic latitudes, where the DM profiles are more robustly constrained, and c) taking into account the large astrophysical uncertainties on the magnetic fields. We have shown that synchrotron emissions can give very pertinent bounds on DM annihilation cross section, confirming previous results [12,[14][15][16].…”
Section: Conclusion and Prospectssupporting
confidence: 90%
“…Emission by small grains of vibrating or spinning dust becomes relevant at even higher frequencies, starting approximately at > ∼ 60 GHz. Synchrotron signal of electron by-products of dark matter WIMP self-annihilation is generally expected to fall in the 100 MHz −100 GHz range (see for example [14]). However, it has been noted in [15,16] that for light dark matter candidates it is beneficial to consider lower frequencies.…”
Section: Synchrotron Radio Emission In the Milky Waymentioning
confidence: 99%
“…We must also take into account that different energy losses of local CREs are used here when compared to Cirelli et al (2010). For CREs with E 1 TeV diffusion can be approximately neglected so that, from the diffusion loss equation, the steady state CRE flux scales approximately linearly with the energy loss timescale τ (see Bergström et al 2009;Borriello et al 2009a). The PAMELA/Fermi regions, instead, scale as the inverse of the local CRE flux.…”
Section: Resultsmentioning
confidence: 99%
“…Such a function is provided on the website [55] in the format btot[E,r,z,gasnorm,MF], where gasnorm allows to change the overall normalization of the gas densities and MF is a flag selecting the magnetic field model. We now recall the different components of this function 4 and illustrate its main features in fig. 2 and 3.…”
Section: An Improved Energy Loss Function For E ± In the Galaxymentioning
confidence: 99%
“…Synchrotron emission has been considered since a long time in regions close to the Galactic Center (GC), characterized by a large intensity of the magnetic field [1]. Its relevance in wider regions of interest in the Galaxy has also been highlighted [2,3,4,5,6,7,8,9,10,11,12]. Bremsstrahlung gamma rays have mostly been neglected for what concerns DM studies.…”
Section: Introductionmentioning
confidence: 99%